GAMBARAN KETAHANAN PANGAN RUMAH TANGGA PETANI PADI DI DESA MALIGAS TONGAH KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN - Entywe Habeahan; Zulhaida Lubis; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The amount of the resulting rice production could not meet the availability of adequate food so that did not reflect the household food security. This study aimed to determine the food expenditures a month to the total household expenditure of farmers, energy and protein consumption of household rice farmers. The research was a descriptive survey, to describe the household food security situation of rice farmers. The samples in this study amounted 76 households from takeable 359 household rice farmers who live in Maligas Tongah Village, Tanah Jawa sub-district, Simalungun district. The data collected was processed and presented in the form of a frequency distribution table which could then be analyzed descriptively. The results showed that the household food security conditions of rice farmers classified bad with vulnerable food 44,7%, household less food 5,3% and food insecurity 9,2%. The level of household food expenditure of rice farmers was 52,6% included high category. The average energy sufficiency level of household rice farmers the included enough category that was 85,5% while the average protein sufficiency level household rice farmers the included less category that was 98,7%. From these results it was suggested to farmers in order to improve the minimum level of dietary protein. The government was expected to provide counseling regarding the nutritional adequacy. Training for productive enterprises to increase household income. keywords: household food security, expenditure, food consumption